Muslim reformist political thought : revivalists, modernists and free will - Khan, Sarfraz (Central Asia research forum series., 2003)
There are two main trends distinguishable amongst Muslim reformists - revivalists and modernists. This book charts and analyses the main trends of Muslim reformist political thought in Bukhara. It is the first to utilize original sources preserved in Soviet archives that were previously inaccessible to western scholars. The author has translated numerous original documents from Tajiki and Russian into English. This book thus serves as a useful resource for students of Islam, Central Asia, the former Soviet Union, and of law, politics and philosophy.